2014
DOI: 10.1515/caslar-2014-0009
|View full text |Cite
|
Sign up to set email alerts
|

A measure of Chinese language learning anxiety: Scale development and preliminary validation

Abstract: As the Foreign

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…A moderate level of disposition toward writing means that students view themselves as surely capable of maintaining an active writing life (Le, 2004;Luo, H., 2014;Pytash & Li, 2014). However, the writing disposition of students may have influenced their writing anxiety.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A moderate level of disposition toward writing means that students view themselves as surely capable of maintaining an active writing life (Le, 2004;Luo, H., 2014;Pytash & Li, 2014). However, the writing disposition of students may have influenced their writing anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The present study demonstrated a positive correlation between anxiety and disposition in writing, but a high correlation does not give researchers the evidence to make a cause-and-effect statement (Chan, 2003). A moderate level of disposition toward writing means that students view themselves as surely capable of maintaining an active writing life (Le, 2004;Luo, H., 2014;Pytash & Li, 2014). However, the writing disposition of students may have influenced their writing anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…The data collection lasted 4 months. A 98-item survey was compiled, including a Chinese Language Learning Anxiety Scale (Luo, 2014), eight subscales adapted from the in-ternational Attitude and Motivation Test Battery (Gardner, 2010), and a background questionnaire. The items on the survey were translated into Chinese by the researcher and back translated by an English teacher at a university in China.…”
Section: Methodsmentioning
confidence: 99%
“…The participant demographics are presented in Table 1. (Luo, 2014). This scale was chosen because it targets Chinese language learning anxiety and measures anxiety in all four skills (i.e.…”
Section: Participantsmentioning
confidence: 99%
“…Learners of foreign language feel uneasy in the foreign language classroom as they find it difficult to speak because they try to avoid errors; such therefore affects their classroom participations. Nervousness is a problem, and it occurs when they are engaged in any of the language skills (Horwitz, Horwtiz & Cope, 1986;Cheng, 2002;Luo, 2014;Chow, Chiu & Wong, 2018), this is witnessed in the clinical experience of Horwitz, Horwtiz & Cope (1986) with speaking and listening, while speaking was identified as to have shown the most frequent level of anxiety. The learners experience anxiety when they find it difficult to discriminate the sounds, the structure and even the content of message of their target language.…”
Section: Introductionmentioning
confidence: 99%